THE ROLE OF MOBILE APPLICATIONS IN IMPROVING THE EDUCATIONAL PROCESS OF HIGHER EDUCATIONAL INSTITUTIONS (ON THE EXAMPLE OF SOLID STATE PHYSICS) - Narkulov, Odil (Журнал иностранных языков и лингвистики, 2022)
This article will consider the possibility of using information and communication technologies in the educational process, in particular, electronic, mobile applications and mobile educational technologies. The content of the initial concepts of the conducted research is defined and presented. Special attention is paid to the mobile application as a modern and effective educational tool. A number of specialized variants of mobile applications that can be used in the educational process are proposed, the positive aspects of their application are identified. A comparative analysis of the available mobile applications used in teaching physics and astronomy is carried out, and the prospects for their use are considered. As a result of the analysis, computer simulation models made on the topic “Crystal structure of solids” are presented, which are the basis for the mobile application “Physics of solids”.